Margaret Truman's Murder on the metro - Land, Jon; Truman, Margaret, 1924-2008 (Truman, Margaret, 1924-2008 Capital crimes series, 2021)
"The nation's first female vice president is dead. The public, including international investigator Robert Brixton, believes it was natural causes, complications related to a long-hidden heart condition. Kendra Rendine, head of Vice President Stephanie Davenport's Secret Service security detail, covertly approaches Brixton to look deeper into Davenport's death. Brixton discovers that a rumored affair between Vice President Davenport and President Corbin Talmidge was actually very much true. Because of this closeness, Davenport saw the devastating deterioration of the President's mental health. She was preparing to invoke the 25th Amendment when she died. Was her death natural causes, or was it murder? Brixton is determined to find out"--